Charged and almost ready: What is holding back the resale market for battery electric vehicles? - Levi Bognar; Scott A. Brave; Thomas H. Klier; Leslie McGranahan (Federal Reserve Bank of Chicago, 2023)
We utilize vehicle registration microdata for all new and used vehicles registered in the U.S. for model years 2010-2022 to study the market for used battery electric vehicles (BEVs). From these records, we establish two stylized facts: 1) BEVs enter the used market at the slowest rate compared to any other powertrain technology, and 2) BEVs are driven significantly less than vehicles featuring other powertrain technologies. We connect these facts through a statistical model of used vehicle registration counts and find that there are significant behavioral differences between BEV and other new vehicle owners in how utilization (both on average and at the margin) leads to these vehicles being resold. By way of a counterfactual exercise that equalizes average vehicle miles traveled, we then illustrate that these behavioral differences can explain from 10-30 percent of the differential rates of transition from new to used vehicle status we observe between BEVs and internal combustion engine (ICE) vehicles.
Keywords: 330